Short-term effects of forest gap size on soil enzyme activity in a Platycladus orientalis plantation - Fei, Fei; Chen, Xinli; Guan, Qingwei (Frontiers in Ecology and Evolution, 2023)
Soil enzymes play a critical role in organic matter decomposition and nutrient cycling in forest ecosystems. However, the effects of forest gaps on soil enzyme activities remain uncertain. This study aims to investigate the short-term effects of forest gap size on soil enzyme activities in Platycladus orientalis plantations. We conducted a study in a 50-year Platycladus orientalis plantation in Xuzhou, sampling soils from three levels of forest gap size (4 m radius, S; 8 m radius, M and 12 m radius, L) at different positions (within gap, edge, and outside the gap) and control plots (CK, no gaps) 2a after the creation of gaps. Soil peroxidase, dehydrogenase, urease, and invertase activities were measured. Specifically, we found that M and S gaps had significantly (P<0.05) higher soil peroxidase activity at the outside position in Apr and Oct, respectively, than CK. Additionally, L gaps had significantly (P<0.05) higher soil dehydrogenase activity at the outside position in Apr than CK. Furthermore, L and S gaps had significantly (P<0.05) higher soil urease activity at the outside position in Oct and Jul, respectively, than CK. Lastly, L and S gaps had significantly (P<0.05) higher soil urease activity at the outside position in Jul than CK. Our findings highlight the significant impact of canopy gaps on soil enzyme activities, which has important implications for forest management and conservation.